The Role of Sultan Oesman Sadiq Syah in Preserving the Bacan Sultanate’s Legacy (1900-1935 AD) - Atim, Arfandi; Warwefubun, Jamain; Misbahuddin, Misbahuddin (Universitas Islam Negeri Sumatera Utara, 2025)
This research to analyze the role of Sultan Oesman Sadiq Syah in preserving the heritage of the Bacan Sultanate (1900-1935). The research was conducted to determine the role of Sultan Oesman Sadiq Syah in preserving the Bacan Sultanate’s legacy (1900-1935). The method used is historical research, namely; heuristics, criticism, interpretation, and historiography, using an oral history approach. The data collected is then analyzed and conclude. The results of the research show that: First, the system of government uses an absolute monarchy system, that is, in every ecstasy the Sultan's leadership will be continued by his direct descendants from a son, who in the Bacan Sultanate is known as